Investigation of the clinical significance and pathological features of lanthanum deposition in the gastric mucosa - Nishida, Shinya (BMC Gastroenterol, 2020)
BACKGROUND: There are often specific endoscopic findings caused by deposition of lanthanum (La) in the gastric mucosa of patients taking lanthanum carbonate (LaC), a novel phosphate binder for patients on hemodialysis. We conducted a retrospective study to investigate the clinical significance of La deposition in the gastric mucosa, and the association between endoscopic features and histologic findings in the same population. METHODS: We compared background factors in patients taking LaC with and without La deposition in their gastroscopic biopsy specimen. We also investigated the relationship between gastric endoscopic biopsy specimens with La deposition and the concurrent endoscopic images. RESULTS: There was a significant difference in the total dose of LaC between the La-positive and La-negative groups (990 g [180–3150 g] vs. 480 g [225–1328 g]; p = 0.013). In 27 biopsy specimens with specific whitish mucosa, 10 showed mild histiocytic infiltration and 17 showed severe infiltration. In contrast, among 24 specimens with non-whitish mucosa, 5 showed no histiocytic infiltration, 10 showed mild infiltration, and 9 showed severe infiltration. There was a significant relationship between endoscopic features and the degree of histiocytic infiltration (p = 0.026). CONCLUSIONS: We demonstrated that La deposition in the gastric mucosa depended on the total dose of LaC and was not affected by background factors. The specific endoscopic features of La deposition are associated with the infiltration of histiocytes, which represents the body’s normal response to foreign bodies. Trial registry The protocol was registered in the University Hospital Medical Information Network Clinical Trial Registry (UMIN000038929, https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000044393).